All we were promised eaudiobook A novel. - Lattimore, Ashton (Books on Tape, 2024)
A housemaid with a dangerous family secret conspires with a wealthy young abolitionist to help an enslaved girl escape, in volatile pre-Civil War Philadelphia—“a gripping novel about standing up to impossible odds” ( People , Best New Books) The rebel . . . the socialite . . . and the fugitive. Together, they will risk everything for one another in this “beguiling story of friendship, deception, and women crossing boundaries in the name of freedom” (Lisa Wingate, #1 New York Times bestselling author of The Book of Lost Friends ). BOOK OF THE MONTH CLUB PICK • ONE OF THE BEST BOOKS OF THE YEAR: The Washington Post, NPR, She Reads Philadelphia, 1837 . After Charlotte escaped from the crumbling White Oaks plantation down South, she’d expected freedom to feel different from her former life as an enslaved housemaid. After all, Philadelphia is supposed to be the birthplace of American liberty. Instead, she’s locked away playing servant to her white-passing father, as they both attempt to hide their identities from slavecatchers who would destroy their new lives. Longing to break away, Charlotte befriends Nell, a budding abolitionist from one of Philadelphia’s wealthiest Black families. Just as Charlotte starts to envision a future, a familiar face from her past reappears: Evie, her friend from White Oaks, has been brought to the city by the plantation mistress, and she’s desperate to escape. But as Charlotte and Nell conspire to rescue her, in a city engulfed by race riots and attacks on abolitionists, they soon discover that fighting for Evie’s freedom may cost them their own.